Successful peficitinib addition on anti-MDA5 antibody-positive dermatomyositis refractory to triple therapy and glucocorticoid reduction. (December 2022) - Oba, Yuki; Yamanouchi, Masayuki; Ikuma, Daisuke; Mizuno, Hiroki; Inoue, Noriko; Sekine, Akinari; Hasegawa, Eiko; Suwabe, Tatsuya; Sawa, Naoki; Ubara, Yoshifumi
Anti-melanoma differentiation–associated gene 5 antibody-positive dermatomyositis is the poorest prognosis of all dermatomyositis due to its associated rapidly progressive interstitial lung disease. Intensive treatment is required from the onset and triple therapy with prednisolone, calcineurin inhibitors, and intravenous cyclophosphamide is recommended. However, some patients are refractory or dependent on this treatment and additional immunosuppressive therapy is required. Recently, the efficacy of tofacitinib, a JAK inhibitor, has been reported. Here, we describe a case of a 50-year-old woman with anti-melanoma differentiation–associated gene 5 antibody-positive dermatomyositis who became refractory to triple therapy and prednisolone reduction, and achieved remission with the addition of peficitinib, a JAK inhibitor. This is the first report showing that peficitinib is effective for anti-melanoma differentiation–associated gene 5 antibody-positive dermatomyositis and it may be a potential treatment option.